Penerapan Metode Simple Multi Attribute Rating Technique (SMART) Untuk Seleksi Penerimaan Bantuan Usaha Produktif - Raihan Mahdy; Fitra Kurnia; Iwan Iskandar; Eka Pandu Cynthia (STMIK Budi Darma, 2023)
Productive business assistance is assistance provided to improve business capabilities, depending on the type of business being running. The goal is to develop work productivity and also increase income. As for the distribution of productive business assistance at BAZNAS Pekanbaru City, it still uses an old system and is not yet effective, so the process takes quite a long process. In order for the selection process to be effective, a decision system was created for the alternative of recipients of productive business assistance. The method in this research using the simple multi attribute rating technique (SMART) method. This research uses 6 criteria and 22 sub-criteria. The application is build with using PHP and MySQL programming languages. The results of the application of the SMART method which has been tested on 10 sample recipients obtained the order of the highest value to the smallest. With the highest value is 0.75. This system has been tested using the Blackbox testing method and the user acceptance test (UAT) with an assessment final value is 94.4%.